2019
DOI: 10.31234/osf.io/h7jfe
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of Acute Transcranial Direct Current Stimulation on Attentional Bias in Pedophilic Disorder: A Pre-registered Pilot Study

Abstract: Individuals with Pedophilic Disorder (PD) experience personal and interpersonal difficulties and are at risk of sexually offending against children. As such, innovative and empirically validated treatments are needed. Recent studies have indicated that sex offenders with child victims (SOC) with PD display an automatic attention bias for child-related stimuli as well as reduced activity in the dorsolateral prefrontal cortex (dlPFC), a brain area involved in cognitive control, including control over sexual arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Both offending and community men might be reluctant to disclosing their sexual attraction to children, albeit for different reasons (e.g., fear of legal repercussions and social desirability, respectively) and this might explain the low concordance. Alternatively, and as argued in a previous study (Pezzoli et al, 2020), it is possible that sexually salient images of children might capture participants' attention more than sexually salient images of adults due to their surprising or disturbing nature, therefore prolonging VTs. In other words, we cannot directly discern whether some fathers gazed longer at child images because of their sexual interest in children or, rather, because those images were particularly surprising or disturbing.…”
Section: The Utility Of Viewing Time Measures To Discriminate Partici...mentioning
confidence: 82%
See 1 more Smart Citation
“…Both offending and community men might be reluctant to disclosing their sexual attraction to children, albeit for different reasons (e.g., fear of legal repercussions and social desirability, respectively) and this might explain the low concordance. Alternatively, and as argued in a previous study (Pezzoli et al, 2020), it is possible that sexually salient images of children might capture participants' attention more than sexually salient images of adults due to their surprising or disturbing nature, therefore prolonging VTs. In other words, we cannot directly discern whether some fathers gazed longer at child images because of their sexual interest in children or, rather, because those images were particularly surprising or disturbing.…”
Section: The Utility Of Viewing Time Measures To Discriminate Partici...mentioning
confidence: 82%
“…The resulting lack of normative data on the link between VTs and sexual interest leaves it unclear how unusual a particular VT pattern might be, therefore making it difficult to establish a critical score that can identify those who are likely to be attracted to children, based on their VT patterns (Seto, 2017a , b ). For instance, one laboratory study found that men attracted to sexually mature adults and men attracted to children gazed longer at child compared to adult sexual stimuli (Pezzoli et al, 2020 ). Conceivably, child sexual stimuli can be highly salient in a non-sexual way (e.g., distressing or disturbing) and, as a result, capture the attention of both sexual interest groups alike.…”
Section: Introductionmentioning
confidence: 99%